Honduras : 2018 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2018)
The IMF-supported program (2014-17) succeeded in reducing Honduras' macroeconomic imbalances. The next step is to adopt institutional reforms to entrench macroeconomic stability to put Honduras on a higher potential growth path.